Home energy management system (ZigBee wireless communication) - Tun, Pyae Win. (2013)
Home energy management with smart devices has been the solution for greener power system. With the support of national interest and funding, it is a great research field that we could contribute. Since the smart grid will be utilized in the future power system, small scale home energy management become a fundamental development area. ZigBee is the only standards-based wireless technology with low cost and power consumption network protocol. The wireless load control and monitoring system in home area network and the pairing communication with the local smart meter is aimed to be developed as part of the home energy management system. The report clearly shows the set up and network configuration for system load control for ZigBee devices and how these modules are integrated with microcontroller for user display. The pairing communication with smart meter in smart energy profile is achieved and the procedure for joining smart energy network is elaborated. Requesting and monitoring of meter data withZigBee cluster library attribute using API is developed. The stimulated smart meter is used due to the limitation of authentication requirement to access the utility smart meter. The meter stimulator is able to establish pairing communication and accessing energy consumption data.